PVC formulary - Wypych, George (ChemTec Publishing, 2014)
PVC Formulary contains invaluable information for PVC manufacturers, processors, and users. It discusses new product development and product reengineering tools and the current state of the market for PVC products. This provides the reader with the critical data they need to formulate successful and durable products, or to evaluate formulations on the background of compositions used by others.Polymer properties determining its proper selection are discussed. Commercial types and grades, polymer forms, and physical-chemical properties of PVC are discussed in detail. All essential information required for the decision-making process is presented in a clear form in order to provide the reader with the necessary data.The book contains over 600 formulations of products belonging to 23 categories derived from characteristic methods of production. A broad selection of formulations is used in each category to determine the essential components of formulations used in a particular method of processing, the most important parameters of successful products, troubleshooting information, and suggestions of further sources of information on the method of processing.A comprehensive and data-rich guide to PVC and its additives, enabling easier and more effective material selection.Over 600 formulations included, along with methods of processing and troubleshooting information.Includes critical data on physical properties, mechanical properties, health and safety, and environmental information for PVC and its products.
Keywords: Polyvinyl chloride.; elektronické knihy; electronic books